Inflation, Interest Rates, and Welfare - Krugman, Paul R.; Persson, Torsten; Svensson, Lars E. O. (Quarterly Journal of Economics, 1985)
This paper develops a simple general equilibrium model of a monetary economy with a capital market. Money demand arises from a “cash-in-advance” constraint rather than from any direct role in the utility function, and uncertainty gives rise to a meaningful portfolio choice between money and bonds. We show that velocity is increasing in the rate of inflation, and that the optimal monetary policy is that which maximizes real balances. We also show that the real rate of interest is not invariant to monetary, policy: inflation lowers the real rate.